Numerical Study of Heat and Moisture Transfer in Textile Materials by a Finite Volume Method (Communications in Computational Physics, 2008)
This paper focuses on the numerical study of heat and moisture transfer inclothing assemblies, based on a multi-component and multiphase flow model whichincludes heat/moisture convection and conduction/diffusion as well as phase change.A splitting semi-implicit finite volume method is proposed for solving a set of nonlinear convection-diffusion-reaction equations, in which the calculation of liquid watercontent absorbed by fiber is decoupled from the rest of the computation. The methodmaintains the conservation of air, vapor and heat flux (energy). Four types of clothingassemblies are investigated and comparison with experimental measurements are alsopresented.